2019
DOI: 10.1111/resp.13540
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for anti‐fibrotic treatment in idiopathic pulmonary fibrosis depends on the predictive equation used for pulmonary function testing

Abstract: Background and objective Publicly funded therapy for idiopathic pulmonary fibrosis (IPF) relies on percentage predicted values from pulmonary function testing, for example Australian patients must have a forced vital capacity ≥50% (%FVC), transfer factor of the lung for carbon monoxide ≥ 30% (%TLco) and forced expiratory volume in 1 s (FEV1)/FVC ratio > 0.7. Despite defined cut‐off values, no jurisdiction prescribes a reference equation for use; multiple equations exist. We hypothesized that access to subsidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Because the registry is conducted in a real-world setting, there was a degree of missing data and variability in follow-up time. Only one equation for calculation of FVC% predicted and one equation for calculation of D l CO % predicted were used, and different reference equations may have provided different results for the proportions of patients in the registry who met inclusion criteria for the INPULSIS and ASCEND trials based on the cutoffs for FVC and D l CO ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the registry is conducted in a real-world setting, there was a degree of missing data and variability in follow-up time. Only one equation for calculation of FVC% predicted and one equation for calculation of D l CO % predicted were used, and different reference equations may have provided different results for the proportions of patients in the registry who met inclusion criteria for the INPULSIS and ASCEND trials based on the cutoffs for FVC and D l CO ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changing from currently utilised reference ranges (for example ECSC) to the GLI reference range will probably lead to differences in the proportion of patients classified as having abnormal lung function. Studies of this issue have been reported for spirometry [37,38] and the single-breath gas transfer test [39][40][41] and all have broadly noted that the impact of changing to GLI equations for these tests varies with age and sex and can impact on the potential eligibility for treatments [42]. Studies assessing the impact of switching to the GLI lung volume equations will be required to help inform health professionals and their patients.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 34 out of 98 patients (total n=528) who were ineligible for treatment using the European Community for Steel and Coal reference set [ 6 ] to calculate FVC % predicted became eligible when using the Third National Health and Nutrition Examination Survery spirometry reference set [ 7 ], and 25 became eligible using the GLI 2012 reference set [ 2 ] instead. The second study from Australia, where antifibrotic lung function eligibility criteria is FVC ≥50% predicted and T LCO ≥30% predicted, found variation in eligibility ranged from 74% to 86% dependent on the reference sets chosen [ 8 ]. Table 3 shows the variation in FVC % predicted and T LCO % predicted in a selection of commonly used reference sets using the presented case's gender, age and height.…”
Section: Discussionmentioning
confidence: 99%